Facial Nerve Outcome and Tumor Control Rate as a Function of Degree of Resection in Treatment of Large Acoustic Neuromas: Preliminary Report of the Acoustic Neuroma Subtotal Resection Study (ANSRS). Issue 2 (28th November 2015) - Monfared, Ashkan; Corrales, Carlton E.; Theodosopoulos, Philip V.; Blevins, Nikolas H.; Oghalai, John S.; Selesnick, Samuel H.; Lee, Howard; Gurgel, Richard K.; Hansen, Marlan R.; Nelson, Rick F.; Gantz, Bruce J.; Kutz, Joe W.; et al.
Abstract: BACKGROUND: Patients with large vestibular schwannomas are at high risk of poor facial nerve (cranial nerve VII [CNVII]) function after surgery. Subtotal resection potentially offers better outcome, but may lead to higher tumor regrowth. OBJECTIVE: To assess long-term CNVII function and tumor regrowth in patients with large vestibular schwannomas. METHODS: Prospective multicenter nonrandomized cohort study of patients with vestibular schwannoma ≥2.5 cm who received gross total resection, near total resection, or subtotal resection. Patients received radiation if tumor remnant showed signs of regrowth. RESULTS: Seventy-three patients had adequate follow-up with mean tumor diameter of 3.33 cm. Twelve received gross total resection, 22 near total resection, and 39 subtotal resection. Fourteen (21%) remnant tumors continued to grow, of which 11 received radiation, 1 had repeat surgery, and 2 no treatment. Four of the postradiation remnants (36%) required surgical salvage. Tumor regrowth was related to non-cystic nature, larger residual tumor, and subtotal resection. Regrowth was 3 times as likely with subtotal resection compared to gross total resection and near total resection. Good CNVII function was achieved in 67% immediately and 81% at 1-year. Better immediate nerve function was associated with smaller preoperative tumor size and percentage of tumor left behind on magnetic resonance image. Degree of resection defined by surgeon and preoperative tumor size showed weak trend toward better late CNVII function. CONCLUSION: Likelihood of tumor regrowth was 3 times higher in subtotal resection compared to gross total resection and near total resection groups. Rate of radiation control of growing remnants was suboptimal. Better immediate but not late CNVII outcome was associated with smaller tumors and larger tumor remnants.